2015
DOI: 10.1055/s-0035-1558645
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy: Current Concepts and Practice Patterns

Abstract: Background Stroke is the number one cause of disability and third leading cause of death among adults in the United States. A major cause of stroke is carotid artery stenosis (CAS) caused by atherosclerotic plaques. Randomized trials have varying results regarding the equivalence and perioperative complication rates of stents versus carotid endarterectomy (CEA) in the management of CAS. Objectives We review the evidence for the current management of CAS and describe the current concepts and practice patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Significantly, the young age of our study participants may provide some explanation. Carotid endarterectomy is considered an effective method for reducing brain stroke risk in patients with severe ICAS [32,33]. Numerous studies have shown its beneficial effect on blood flow in the ophthalmic artery, central retinal artery, posterior ciliary arteries, and chorioretinal circulation using Doppler ultrasonography and laser speckle flowgraphy [21,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the young age of our study participants may provide some explanation. Carotid endarterectomy is considered an effective method for reducing brain stroke risk in patients with severe ICAS [32,33]. Numerous studies have shown its beneficial effect on blood flow in the ophthalmic artery, central retinal artery, posterior ciliary arteries, and chorioretinal circulation using Doppler ultrasonography and laser speckle flowgraphy [21,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, although we are able to show that there are changes in some of these parameters we are not able to determine the clinical significance of these parameters in this preliminary study. The study also showed that using these parameters there was a difference between the two approaches to the treatment of carotid stenosis, ( Saha et al, 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the adaptability of the brain, there is still a 2.1% risk of peri-operative major stroke and death with endarterectomy from either a hypoperfusion or embolic etiology, ( Ferguson et al, 1999 ). During the endovascular procedure there is no equivalent of clamping, although there may often be a period of angioplasty which for a brief period of time does occlude the blood supply to the brain, ( Saha et al, 2015 ). In many centres a device is deployed distal to the stent to capture any emboli dislodged during the deployment of the stent or angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Awake carotid endarterectomy (CEA) under regional anesthesia (RA) is a challenging procedure as it is often associated with increased peri-operative stress. 1,2 The stress response to CEA is generally abolished within 24 h. 2,3 Elevated systemic cortisol level reflecting intraoperative stress response, directly correlates with cerebral hypoperfusion during carotid artery cross-clamping. 3 Therefore, attenuation of the stress response to CEA might decrease the incidence of cerebral ischemic events.…”
Section: Introductionmentioning
confidence: 99%